2016
DOI: 10.18632/oncotarget.7071
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-326 targets CCND1 and inhibits non-small cell lung cancer development

Abstract: Hsa-miRNA-326 (miR-326) has recently been discovered having anticancer efficacy in different organs. However, the role of miR-326 on non-small cell lung cancer (NSCLC) is still ambiguous. In this study, we investigated the role of miR-326 on the development of NSCLC. The results indicated that miR-326 was significantly down-regulated in primary tumor tissues and very low levels were found in NSCLC cell lines. Ectopic expression of miR-326 in NSCLC cell lines significantly suppressed cell growth as evidenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 58 publications
6
69
0
Order By: Relevance
“…Wu et al (23) reported that miR-326 re-expression attenuated cell growth and motility and promoted cell apoptosis and cell cycle-arrest in colorectal cancer. Studies revealed that miR-326 decreased cell proliferation, viability, colony formation, migration and invasion, reversed chemoresistance and increased apoptosis and epithelial-to-mesenchymal transition of lung cancer (25,(44)(45)(46). These findings indicated that miR-326 could be developed as a therapeutic target for these human cancer types.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Wu et al (23) reported that miR-326 re-expression attenuated cell growth and motility and promoted cell apoptosis and cell cycle-arrest in colorectal cancer. Studies revealed that miR-326 decreased cell proliferation, viability, colony formation, migration and invasion, reversed chemoresistance and increased apoptosis and epithelial-to-mesenchymal transition of lung cancer (25,(44)(45)(46). These findings indicated that miR-326 could be developed as a therapeutic target for these human cancer types.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, low miR-326 expression is an independent factor predicting poor prognosis for glioma patients (40). Downregulation of miR-326 is also observed in colorectal (23), pancreatic (24) and lung cancer (25). Previous studies have indicated that miR-326 may be investigated as a useful prognostic marker in human cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BrdU incorporation ELISA assay [33] was performed, and results show that Palomid 529 dosedependently inhibited 786-O cell proliferation (Fig. 1C).…”
Section: Palomidmentioning
confidence: 92%